2022
DOI: 10.31235/osf.io/2r98w
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Digital discretion and public administration in Africa: Implications for the use of artificial intelligence

Abstract: The digitalisation of public services is implicated in fundamental changes to how civil servants make decisions and exercise discretion. Most significant has been a shift in responsibility away from ‘street-level bureaucrats’ to ‘system-level bureaucrats’; a technology-savvy community of officials, consultants and private enterprises involved in the design of information technology systems and associated rules. The relatively recent inclusion of artificial intelligence (AI) and data-driven algorithms raises ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…The humanitarian sector in Togo leverages machine learning algorithms and mobile phone data for effective aid distribution. Despite numerous startups in Western Africa, [28] found that most of these countries are missing from the MI ecosystem. [29] reports the following number of companies that specialize in MI in Western Africa: Nigeria: 456, Ghana: 115, Ivory Coast: 29, Senegal: 23.…”
Section: H Republic Of Thementioning
confidence: 99%
“…The humanitarian sector in Togo leverages machine learning algorithms and mobile phone data for effective aid distribution. Despite numerous startups in Western Africa, [28] found that most of these countries are missing from the MI ecosystem. [29] reports the following number of companies that specialize in MI in Western Africa: Nigeria: 456, Ghana: 115, Ivory Coast: 29, Senegal: 23.…”
Section: H Republic Of Thementioning
confidence: 99%